Trabalho e (i)migração: determinações do movimento migratório de bolivianos da cidade de São Paulo para Guarulhos - Silva, Fabiana Aparecida da (2012)
This study sought to ascertain the determinations of the migratory movement of Bolivian immigrants in São Paulo to Guarulhos. The theoretical development is based on the Social Theory of Marx, especially in its consideration of Work and Culture who helped in the analysis of the phenomena of (i)migration in the context of Bolivia and Brazil. We investigated the process of labor exploitation and class domination that characterize the daily lives of Bolivian immigrants in sewing workshop in São Paulo, in Guarulhos and neighboring municipalities. The aim is also to present the human rights violations in this context and contribute to Social Services intervention in uncompromising defense of these rights and principles of professional ethics